2022
DOI: 10.1101/2022.10.31.514244
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A mesocorticolimbic signature of pleasure in the human brain

Abstract: Pleasure is a fundamental driver of human behavior, yet its neural basis remains largely unknown. Rodent studies highlight opioidergic neural circuits connecting the nucleus accumbens, ventral pallidum, insula, and orbitofrontal cortex as critical for the initiation and regulation of pleasure, and human neuroimaging studies exhibit some translational parity. However, whether activation observed across these regions reflects a common, generalizable code for pleasure driven by opioidergic mechanisms remains uncl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 168 publications
(246 reference statements)
2
5
0
Order By: Relevance
“…Together, these findings are broadly consistent with studies reporting the amygdala is involved in reward learning and evaluating social images (Baxter and Murray, 2002;Adolphs and Spezio, 2006). They are also congruent with work in nonhuman primates showing that both pleasant and unpleasant stimuli engage distributed neural populations in the amygdala (Paton et al, 2006;Belova et al, 2008), and with fMRI evidence showing that the amygdala participates in a distributed network of brain regions sensitive to fluctuations in hedonic valence (Kragel et al, 2023).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Together, these findings are broadly consistent with studies reporting the amygdala is involved in reward learning and evaluating social images (Baxter and Murray, 2002;Adolphs and Spezio, 2006). They are also congruent with work in nonhuman primates showing that both pleasant and unpleasant stimuli engage distributed neural populations in the amygdala (Paton et al, 2006;Belova et al, 2008), and with fMRI evidence showing that the amygdala participates in a distributed network of brain regions sensitive to fluctuations in hedonic valence (Kragel et al, 2023).…”
Section: Discussionsupporting
confidence: 88%
“…Future studies using different movies, videos, or other dynamic visual stimuli to train encoding models are needed to identify the set of variables encoded by the amygdala, and to assess the extent to which they are context dependent or generalize across stimulus types (Čeko et al, 2022) and situations (Kragel et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, multivariate predictive modeling, a machine learning technique based on MVPA, is suggested to be more suitable for identifying neuromarkers for specific subjective emotional states with high effect sizes and clinical significance by providing predictions (instead of local mapping) about emotional experience from distributed neural activity patterns 51,57 . Chang et al showed for instance that a whole-brain multivariate model explained much more variance in predicting experiencing negative affect than local regions 51,52 , and this predictive modeling approach has been successfully utilized to develop models that can sensitively and specifically predict subjective experiences of fear 21 ,pain 53 and pleasure 58 .…”
Section: Introductionmentioning
confidence: 99%
“…The potential utility of neuromarkers for examining mindfulness effects are not limited to the example of somatic pain. Other neuromarkers have been developed for observed pain, negative affect, reward and pleasure (37)(38)(39)(40). In particular, a neuromarker called the Neural Craving Signature (NCS), comprising a multivariate pattern of activity involving regions previously established to be involved in reward and addiction (ventromedial PFC, ventral striatum, dorsal anterior cingulate), provides a predictive model of food and drug craving states (41).…”
Section: Figure 3 Developing and Validating A Population-level Neurom...mentioning
confidence: 99%